Flagellum-Independent Surface Migration of Vibrio cholerae and Escherichia coli - Brown, Igor I. (American Society for Microbiology, 2001)
Surface translocation has been described in a large variety of microorganisms, including some gram-negative enteric bacteria. Here, we describe the novel observation of the flagellum-independent migration of Vibrio cholerae and Escherichia coli on semisolid surfaces with remarkable speeds. Important aspects of this motility are the form of inoculation, the medium composition, and the use of agarose rather than agar. Mutations in several known regulatory or surface structure proteins, such as ToxR, ToxT, TCP, and PilA, did not affect migration, whereas a defect in lipopolysaccharide biosynthesis prevented translocation. We propose that the observed surface migration is an active process, since heat, protease, or chloramphenicol treatments of the cells have strong negative effects on this phenotype. Furthermore, several V. cholerae strains strongly expressing the hemagglutinin/protease but not their isogenic hap-negative mutants, lacked the ability of surface motility, and the treatment of migrating strains with culture supernatants from hap strains but not hap-null strains prevented surface translocation.